Simeon's gift - Andrews, Julie 1935-; Hamilton, Emma Walton 1962- (HarperCollinsPublishers, 2003)
A humble musician sets out to find the perfect gift for the woman he loves and is overwhelmed by all he sees, until he discovers within himself his true gift.
Keywords: Musicians -- Fiction; Self-realization -- Fiction; Bilderbuch; Kinderbuch